2009
DOI: 10.1614/wt-08-174.1
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvants Influenced Saflufenacil Efficacy on Fall-Emerging Weeds

Abstract: Saflufenacil is a new herbicide being developed for preplant burndown and PRE broadleaf weed control in field crops, including corn, soybean, sorghum, and wheat. Field experiments were conducted in 2006 and 2007 at Concord, in northeast Nebraska, with the objective to describe dose–response curves of saflufenacil applied with several adjuvants for broadleaf weed control. Dose–response curves based on log-logistic model were used to determine the effective dose that provides 90% weed control (ED90) values for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 16 publications
2
35
0
Order By: Relevance
“…Glyphosate applied alone only provided 76% control of field pennycress (Table 3), while addition of 20 g ai/ha of saflufenacil to glyphosate improved weed control efficacy (Table 3). Similarly, others reported that 90% control of field pennycress was achieved with saflufenacil doses of 103 and 34 g ai/ha applied alone or with MSO to the 5 to 8 cm diameter rosette (15).…”
Section: Field Pennycress Controlmentioning
confidence: 95%
See 2 more Smart Citations
“…Glyphosate applied alone only provided 76% control of field pennycress (Table 3), while addition of 20 g ai/ha of saflufenacil to glyphosate improved weed control efficacy (Table 3). Similarly, others reported that 90% control of field pennycress was achieved with saflufenacil doses of 103 and 34 g ai/ha applied alone or with MSO to the 5 to 8 cm diameter rosette (15).…”
Section: Field Pennycress Controlmentioning
confidence: 95%
“…Addition of 20 g ai/ha dose of saflufenacil provided a slight improvement of control (90%) (Table 2). Knezevic et al (15) also concluded that fall applications of saflufenacil to the 5 to 8 cm tall henbit required 98 and 35 g ai/ha for saflufenacil applied alone and with MSO for obtaining 90% control.…”
Section: Henbit Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Varshney and Singh (1990) found 67% reduction in weed biomass by adding the isoctyl phenyl polyethoxy ethanol adjuvant in 33% reduced rates of terbutryn, isoproturon, methabenzthiazuron and metoxuron compared with the herbicide alone. Among different adjuvants used, Knezevic et al (2009) found the highest improvement in efficacy of saflufenacil against field bindweed in wheat by addition of methylated seed oil. There is little or no information available about the effect of the alkyl ether sulfate adjuvant when used with herbicides in wheat crop for controlling common goosefoot and field bindweed.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of herbicides can be enhanced using surfactants (Knezevic et al, 2009;Loken, HattermanValenti, 2013;Gitsopoulos et al, 2014). Enhancement of herbicidal activity by surfactants may be related to improving the dose transfer process (absorption) of active ingredient on weed leaves (McCullough, Hart, 2009).…”
Section: Introductionmentioning
confidence: 99%